Analisis Komparatif Abnormal Return dan Trading Volume Activity berdasarkan Political Event (Event Study pada Pengesahan RUU KPK 2019) - Hafidz, Maulana Faizal; Isbanah, Yuyun (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This research aims to analyze the reaction of the Indonesia capital market with average abnormal return (AAR) and cumulative abnormal return (CAR) before-after the legality of KPK law revision in 2019. This research also using trading volume activity to describe the react of capital market before-after the legality of KPK law revision in 2019. This research use event study for analysis method with 5 days before and 5 days after the event with secondary data from the Indonesia capital market. The research testing by Paired Sample T-Test and Kolmogorov-Smirnov. The result of Kolmogorov-Smirnov shows that AAR, CAR, and TVA are normal distribution. The result of the paired sample t-test shows that no difference between average abnormal return and trading volume activity before-after the political event because investors already get bad news on before and after the legality of KPK law revision in 2019 which make investor wait and see. But, the paired sample t-test shows the difference between CAR before-after the legality of KPK law revision in 2019, because the investor gets a positive abnormal return on t-3 and t-4 which make a different cumulative abnormal return.